2010
DOI: 10.1061/(asce)hy.1943-7900.0000149
|View full text |Cite
|
Sign up to set email alerts
|

Case Study: Movable Bed Model Scaling for Bed Load Sediment Exclusion at Intake Structure on Rio Grande

Abstract: Results of a laboratory modeling study are presented for excluding bed load sediment from a diversion/intake structure on the Rio Grande in Albuquerque, New Mexico. To achieve model similitude, crushed coal was used to model the prototype sediment in a 1:24 scaled model with an exaggerated slope such that shear force is adequately modeled. The Shields parameters and critical Shields parameters were matched between the prototype and the model, resulting in similar grain Reynolds numbers. Twenty-four tests, wher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…evaluated different forms of habitat creation along a curvilinear deviation caused in a shallow water channel. Ho et al (2010), in a distorted model, found ways to desalinate a water intake. Armanini et al (2010) studied the influence of breakwaters to improve the navigation condition on the Po River in Italy.…”
Section: Introductionmentioning
confidence: 99%
“…evaluated different forms of habitat creation along a curvilinear deviation caused in a shallow water channel. Ho et al (2010), in a distorted model, found ways to desalinate a water intake. Armanini et al (2010) studied the influence of breakwaters to improve the navigation condition on the Po River in Italy.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of vanes on scour and sediment control has tested by many researchers; Voisin and Townsend (2002) introduced the best dimensions of submerged vanes to protect the outer river banks in bend sections. Coonrod et al (2010) constructed a physical model of the Reo Grand River to investigate the effect of submerged vanes to control sediment movement within bends. The characteristics of the flow and sediment motion around the vanes by using laboratory model were studied by Tan et al (2005).…”
Section: Introductionmentioning
confidence: 99%